THEORETICAL AND METHODOLOGICAL APPROACHES TO ANALYSIS OF SOMATIC COMPONENT UNITS (Modern American Journal of Linguistics, Education, and Pedagogy, 2025)
This study is devoted to the study of linguistic and linguistic features of somatic component linguistic units on the basis of modern linguistic approaches. The work analyzes the close relationship between language and culture within the framework of linguistic and linguistic poetics, defining the role of somatic units in the expression of national mentality, cultural values, artistic and aesthetic thought. The study covers the theoretical foundations of the concept of somatic component and shows the manifestation of such units at the lexical, phraseological and metaphorical-symbolic levels. Also, units with somatic components are classified on the basis of anatomical, semantic-functional and speech application criteria, special attention is paid to revealing their semantic scope and functionality. The results of the research serve to reveal the multidimensional nature of units with somatic components in the linguistic system, as well as to a deeper interpretation of them in linguistic and lingvopoetic terms.